A modeling approach to assess coastal management effects on benthic habitat quality: A case study on coastal defense and navigability. (5th January 2017) - Cozzoli, Francesco; Smolders, Sven; Eelkema, Menno; Ysebaert, Tom; Escaravage, Vincent; Temmerman, Stijn; Meire, Patrick; Herman, Peter M.J.; Bouma, Tjeerd J.
Abstract: The natural coastal hydrodynamics and morphology worldwide is altered by human interventions such as embankments, shipping and dredging, which may have consequences for ecosystem functionality. To ensure long-term ecological sustainability, requires capability to predict long-term large-scale ecological effects of altered hydromorphology. As empirical data sets at relevant scales are missing, there is need for integrating ecological modeling with physical modeling. This paper presents a case study showing the long-term, large-scale macrozoobenthic community response to two contrasting human alterations of the hydromorphological habitat: deepening of estuarine channels to enhance navigability (Westerschelde) vs. realization of a storm surge barrier to enhance coastal safety (Oosterschelde). A multidisciplinary integration of empirical data and modeling of estuarine morphology, hydrodynamics and benthic ecology was used to reconstruct the hydrological evolution and resulting long-term (50 years) large-scale ecological trends for both estuaries over the last. Our model indicated that hydrodynamic alterations following the deepening of the Westerschelde had negative implications for benthic life, while the realization of the Oosterschelde storm surge barriers had mixed and habitat-dependent responses, that also include unexpected improvement of environmental quality. Our analysis illustrates long-term trends in the natural community caused by opposing management strategies. The divergent human pressures on the Oosterschelde and Westerschelde are examples of what could happen in a near future for many global coastal ecosystems. The comparative analysis of the two basins is a valuable source of information to understand (and communicate) the future ecological consequences of human coastal development. Graphical abstract: